Research on Judge's Decision-making Factors and Judicial Justice Evaluation from the Perspective of Legal Psychology - Liu, Yaya (International Journal of Social Sciences and Public Administration, 2024)
From the unique and often overlooked lens of legal psychology, this paper delves deep into the intricate web of factors that shape and influence judges' decision-making processes. It meticulously examines how, while legal knowledge and professional experience form the bedrock of judicial rulings, they are not the sole or even the primary determinants of judicial outcomes.Instead, the paper argues that a judge's decisions are often subtly, yet profoundly, influenced by psychological factors and their deeply ingrained personal social backgrounds. These factors, ranging from unconscious biases to societal pressures, can have a significant impact on how a judge interprets the law and applies it to specific cases.This nuanced understanding of the judges' decision-making processes underscores the inherent complexity of evaluating judicial impartiality. The study posits that a truly comprehensive assessment of judicial fairness demands a multifaceted approach that goes beyond surface-level critiques and encompasses a wide range of standards, methodologies, and perspectives.